Incidental Finding of Lamellar Calcification of the Falx Cerebri Leading to the Diagnosis of Gorlin-Goltz Syndrome - I. Saulite; B. Voykov; T. Mehra; W. Hoetzenecker; E. Guenova (Karger Publishers, 2013)
Here, we report the case of an incidental finding of lamellar calcification of the falx cerebri in a routine computed tomography scan of the head after an accidental trauma. This lamellar calcification led to the diagnosis of Gorlin-Goltz syndrome (GGS) in the patient and her daughter. Lamellar calcification of the falx cerebri is a pathognomonic feature of GGS. Our case report highlights the importance of a multidisciplinary diagnostic approach to GGS.